Delivery of radix ophiopogonis polysaccharide via sucrose acetate isobutyrate-based in situ forming systems alone or combined with its mono-PEGylation - LiNa Wang; Xiao Zheng; Fei Wu; Lan Shen; Xiao Lin; Yi Feng (Taylor & Francis Group, 2018)
This work aimed to achieve long-lasting delivery of radix ophiopogonis polysaccharide (ROP) by sucrose acetate isobutyrate (SAIB)-based in situ forming systems (ISFSs) alone or combined with mono-PEGylation of ROP. When the '90%SAIB/10% solvent' system was used, the mean residence time (MRT) of ROP was prolonged by 4.3 5 ∼ 7.00 times and the initial release rate was reduced significantly. However, this system was only suitable for days-long sustained release of ROP in short-term therapy. As to the 'SAIB/additives/solvent' system containing mono-PEGylated ROP, the results indicated that SAIB/poly(d,l-lactide-co-glycolide) (PLGA)/N-methyl-2-pyrrolidone (NMP) was superior to SAIB/polylactic acid (PLA)/NMP and SAIB/PLA/ethanol in controlled release. Moreover, weeks- to months-long (16-60 d) smooth release of ROP could be achieved by varying the concentration (10-30%) and molecular weight (MW) of PLGA (10-50 kDa) or by employing a moderate MW of PEGylated ROP (∼20 or ∼30 kDa). With further increasing the conjugate MW to ∼40 kDa, the contribution of drug elimination to its plasma retention seemed to surpass that of the SAIB-based system, resulting in that the system no longer had an obvious influence on the in vivo behavior of the conjugate. Besides, the results of host response confirmed that with less solvent being used, the SAIB-based systems showed a higher biocompatibility than the PLGA-based systems, suggesting that they could be freely chosen in the prevention and/or cure of chronic diseases.